Studies of Backward Particle Production with a Fixed-Target Experiment Using the LHC Beams - Federico Alberto Ceccopieri (Advances in High Energy Physics)
The foreseen capability to cover the far backward region at a Fixed-Target Experiment using the LHC beams allows one to explore the dynamics of the target fragmentation in hadronic collisions. In this report we briefly outline the required theoretical framework and discuss a number of studies of forward and backward particle production. By comparing this knowledge with the one accumulated in Deep Inelastic Scattering on target fragmentation, the basic concept of QCD factorisation could be investigated in detail.